Challenges in the development of treatment guidelines for bipolar disorder - Fountoulakis, Konstantinos N.; Fountoulakis, Nikolaos K.; Antoniadis, Diomidis (Frontiers in Psychiatry, 2025)
Bipolar disorder (BD) is such a complex mental disorder, that even the development of true, reliable, and valid treatment guidelines seems to be a goal almost impossible to achieve. The challenges include the complexity and uniqueness of the clinical picture and the therapeutical options available, special issues including gender, pregnancy, and the different views of therapists and patients. An additional issue is the method for the development of the guidelines, with systematic reviews of the hard evidence to constitute the most recent trend. The grading of the literature findings could be crucial for the whole process, as it is often ‘contaminated’ by expert opinion. Unfortunately, in the literature, BD is treated as a fragmented condition and each fragment is studied separately as if it were independent. This, in combination with incomplete reporting of the findings, makes the synthesis of the landscape almost impossible and the development of a comprehensive single algorithm for the continuous treatment of BD, extremely difficult. Overall, developing treatment guidelines for BD constitutes a great challenge. This task demands an exhaustive review of the existing literature, searching for unpublished data and digging deep into them to comprehend their nature. It also needs to manage to synthesize the fragmented research picture that refers to isolated faces of the disorder, into a comprehensive network of decision-making that will incorporate the knowledge of the past with decisions for the present by having the mind in the future (the three-fingers rule).